Burden of scabies in a Ghanaian penitentiary. - Yaw Ampem Amoako; Michael Ntiamoah Oppong; Dennis Odai Laryea; Gloria Kyem; Solomon Gyabaah; Abigail Agbanyo; Bernadette Agbavor; Nana Konama Kotey; Irene Dzathor; Felicia Owusu-Antwi; Kingsley Asiedu; Richard Odame Phillips; et al. (PLoS ONE)
Background There is a dearth of information concerning the epidemiology of human scabies in prisons. Therefore, we aimed to assess the burden of scabies and ascertain if prevalence was high enough to warrant mass drug administration (MDA) with ivermectin in a medium security prison in central Ghana. Methods We conducted a cross-sectional study in December 2022 and recruited inmates at the Kumasi central prison in Ghana. Medical history and demographic information was collected using a REDCap questionnaire. A standardised skin examination of exposed regions of the body was performed on all participants and scabies was diagnosed based on the criteria of the International Alliance for the Control of Scabies (IACS). Results Of the 559 participants, 19 (3.4%) were female. The median (IQR) age was 36 (33-40) years. There were 368 cases (65.8%) of scabies which was mostly located on the hands, fingers and finger webs. No female inmate had scabies. Scabies severity was predominantly mild (63.3%) or moderate (30.7%). Among males, the median (IQR) number of persons per cell was 115 (56-118) and 7 (7-8) for female prisoners. 79.2% of 96 individuals previously treated in the preceding two months still demonstrated skin manifestations of scabies. Impetigo was found in 12.9% of participants. Seventeen percent of participants with scabies had impetigo compared to 5.8% in individuals without scabies [RR 2.9 (95% CI 1.6-5.5)]. Conclusion A very high proportion of inmates suffered from scabies in the prison. MDA with ivermectin and health education are needed to reduce the burden of scabies in the prison. Its implementation and effectiveness should be studied.